Global assessment of agricultural system redesign for sustainable intensification - Pretty, Jules; Benton, Tim G.; Bharucha, Zareen Pervez; Dicks, Lynn V.; Flora, Cornelia Butler; Godfray, H. Charles J.; Goulson, Dave; Hartley, Sue; Lampkin, Nic; Morris, Carol; Pierzynski, Gary; Prasad, P.V. Vara; et al. (Springer Nature, 2018)
The sustainable intensification of agricultural systems offers synergistic opportunities for the co-production of agricultural and natural capital outcomes. Efficiency and substitution are steps towards sustainable intensification, but system redesign is essential to deliver optimum outcomes as ecological and economic conditions change. We show global progress towards sustainable intensification by farms and hectares, using seven sustainable intensification sub-types: integrated pest management, conservation agriculture, integrated crop and biodiversity, pasture and forage, trees, irrigation management and small or patch systems. From 47 sustainable intensification initiatives at scale (each >104 farms or hectares), we estimate 163 million farms (29% of all worldwide) have crossed a redesign threshold, practising forms of sustainable intensification on 453 Mha of agricultural land (9% of worldwide total). Key challenges include investment to integrate more forms of sustainable intensification in farming systems, creating agricultural knowledge economies and establishing policy measures to scale sustainable intensification further. We conclude that sustainable intensification may be approaching a tipping point where it could be transformative.